PENGEMBANGAN CERITA BERGAMBAR BERBASIS NILAI KARAKTER SEBAGAI PENUNJANG LITERASI - Mila Aulani; Burhanuddin; Zulfadli Hamdi; Yul Alfian Hadi (PGSD UNIKA SANTU PAULUS RUTENG, 2021)
This study is research and development. This study aims to describe the procedure of picture story development based character value as support literacy in SDN 3 Teros. This study used Borg and Gall development which divided into seven stages those were analysis of need, planning, product development, limited test, revise of product result, main product testing, and revise last product. The instrument of this study was interview sheet and questionnaire. The interview was used to conduct analysis of need, while the questionnaire was used to validate product and observe students towards picture story book which was developed by researcher. The result showed that linguist “4.5”, media expert “4.7”, practicality assessment “4.1” and the result of questionnaire “4.4”. Based on the data which was developed by the researcher was “appropriate” with the score from “4.1-4.7”. It can be concluded that the product can be used as reading resources to support literacy community in SDN 3 Teros in academic year 2020/2021.